To what Degree are African Researchers Publishing in Open Access Journals since the launch of Plan S? - Owango, Joy (My University, 2020)
There is an ongoing digital disruption in Higher Education with the demand for #Openscience systems & Open Access data. Since the launch of Plan_S (https://coalition-s.org) in Sep 2018, are African researchers taking advantage of this and publishing in Open Access journals? What are the trends? This presentation was held at the 2020 SARIMA VIRTUAL CONFERENCE, August 4-6, 2020.
Keywords: Open Access; Journal Publishing; Africa